Health-related quality of life of children with X-linked hypophosphatemia in Germany - Klein, Martin; Obermaier, Michael; Mutze, Helena; Wilden, Sophia Maria; Rehberg, Mirko; Schlingmann, Karl Peter; Schmidt, Dorothee; Metzing, Oliver; Hübner, Angela; Richter-Unruh, Anette; Kemper, Markus J.; Weitz, Marcus; et al. (Pediatric nephrology, 2024)
BACKGROUND: X-linked hypophosphatemia (XLH) is a rare inherited phosphate-wasting disorder associated with bone and dental complications. Health-related quality of life (HRQoL) is reduced in XLH patients on conventional treatment with phosphate supplements and active vitamin D, while information on patients treated with burosumab is rare. - METHODS: HRQoL was assessed in 63 pediatric XLH patients participating in a prospective, observational study and patient registry in Germany using the KIDSCREEN-52 survey instrument and standardized qualitative interviews. - RESULTS: The median age of the XLH patients was 13.2 years (interquartile range 10.6 - 14.6). At the time of the survey, 55 (87%) patients received burosumab and 8 (13%) conventional treatment. Forty-six patients (84%) currently being treated with burosumab previously received conventional treatment. Overall, HRQoL was average compared to German reference values (mean ± SD: self-report, 53.36 ± 6.47; caregivers' proxy, 51.33 ± 7.15) and even slightly above average in some dimensions, including physical, mental, and social well-being. In general, XLH patients rated their own HRQoL higher than their caregivers. In qualitative interviews, patients and caregivers reported that, compared with conventional therapy, treatment with burosumab reduced stress, bone pain, and fatigue, improved physical health, and increased social acceptance by peers and the school environment. - CONCLUSIONS: In this real-world study in pediatric XLH patients, HRQoL was average or even slightly above that of the general population, likely due to the fact that the vast majority of patients had their treatment modality switched from conventional treatment to burosumab resulting in improved physical health and well-being.
Gesehen am 21.02.2025